2022
DOI: 10.3390/antiox11020398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Solvent Extracts and Major Bioactive Components from Portulaca oleracea for Antioxidant, Anti-Tyrosinase, and Anti-α-Glucosidase Activities

Abstract: Portulaca oleracea is a well-known species for traditional medicine and food homology in Taiwan. In traditional medicine, P. oleracea is also used to treat gastrointestinal disorders, liver inflammation, fever, severe inflammation, and headaches. We investigated antioxidant, anti-tyrosinase, and anti-α-glucosidase activities of various solvent extracts and major bioactive components from P. oleracea. Ethanol and acetone extracts showed potent DPPH, ABTS, and hydroxyl radical scavenging activities. Chloroform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…However, antioxidants in the body fail to remove free radicals completely once the body’s immunity is weakened or invaded by toxic substances, such as Cd and Hg, and the intake of foods rich in antioxidants can make up for this deficiency. Notably, the extensive application of artificial antioxidants in the food industry may cause liver damage and cancer [9] . This study assessed the antioxidant and antifungal activities of A. membranaceus stem and leaf extracts to provide a possible innovative application for the development of natural antioxidants from A. membranaceus by-products, encourage recycling, and reduce the environmental impact of waste disposal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, antioxidants in the body fail to remove free radicals completely once the body’s immunity is weakened or invaded by toxic substances, such as Cd and Hg, and the intake of foods rich in antioxidants can make up for this deficiency. Notably, the extensive application of artificial antioxidants in the food industry may cause liver damage and cancer [9] . This study assessed the antioxidant and antifungal activities of A. membranaceus stem and leaf extracts to provide a possible innovative application for the development of natural antioxidants from A. membranaceus by-products, encourage recycling, and reduce the environmental impact of waste disposal.…”
Section: Discussionmentioning
confidence: 99%
“…At present, synthetic antioxidants, such as butylated hydroxy anisole (BHA) and butylated hydroxy toluene (BHT), are widely used in food production and processing. However, studies have shown that the widespread use of synthetic antioxidants may cause liver damage and cancer [9] . Therefore, natural food antioxidants with high safety, strong antibacterial ability, and absence of side effects have attracted considerable research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Based on phytochemical studies, the yield and the antioxidant activity of a plant extract depend on the selected extraction solvent [65][66][67]. Diferent solvents are employed to isolate diferent antioxidant compounds based on their disparities in polarities [68]. In this study, dichloromethane solvents were used as a midpolar solvent for extraction of polyphenols and other midpolar phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…They are also the precious resource for new drug research and development. It is reported that many TCMs like mulberry leaves, Catechu , Portulaca oleracea, and Cornus officinalis exhibit good inhibitory activity on α-glucosidase. However, it is challenging to promptly and accurately discover the target active ingredients in complex TCMs.…”
Section: Introductionmentioning
confidence: 99%